Efektivitas Vitamin C Pada Daun Kelor Terhadap Bilangan Peroksida Dari Minyak Jelantah - Nastiti Kartikorini (Universitas Muhammadiyah Surabaya, 2019)
Used cooking oil is a cooking oil that has been used several times. Used cooking oil undergoes an oxidation reaction to produce high peroxide compounds. Phenolic compounds are primary antioxidants contained in Moringa leaves which slow the oxidation down in used cooking oil so that it can be stored longer. Formulation of the problem in this study was whether there was an inhibitory test on Moringa oleifera Leaves powder on the peroxide value in used cooking oil. The purpose of this study was to determine the inhibition of Moringa leaves powder to peroxide value on used cooking oil. This type of research was an experimental i.e. to determine whether there was the inhibition of Moringa leaves powder to the peroxide value in used cooking oil. The sample in this study was 5 samples from 6 fried traders, and repeated 5 times so that the total sample was 25 samples. Peroxide levels could be decreased due to the antioxidant content found in Moringa leaves. Antioxidants found in Moringa leaves are phenolic components. Phenolic components can inhibit free radicals and inhibit peroxide value to decrease. Moringa was suitable for areas where strong and long winds, drought occur simultaneously, and cause serious soil erosion. Nutrient content in deciduous leaves could fertilize and improve marginal soil quality (Dudi, 2015). Therefore, Moringa leaves not only have high antioxidants but also could be found easily in Surabaya. From the results of peroxide levels test, it was known that the average peroxide value in used cooking oil without Moringa leaves was equal to 23,9957 mEq and with Moringa leaves by different time variation i.e. 1 day (14,3182 mEq), 2 days (10,7987 mEq), 3 days (6,1593 mEq), 4 days (3,0397 mEq). Statistical analysis with Anova test showed the inhibition of Moringa leaves powder to decrease in peroxide value on used cooking oil with a value of p (sig) = 0,000 which was less than 0.05. Based on the results of the Tukey HSD test, the most effective soaking of Moringa leaves powder for 4 days was to reduce peroxide levels in used cooking oil by giving 5gr Moringa leaf powder with 100ml used cooking oil. Keywords : Levels of Peroxide Value, Moringa Leaves, Used Cooking Oil